Prevalence of Moderate and Acute Suicidal Ideation among a National Sample of Tribal College and University Students 2014–2015. Issue 3 (3rd July 2021) - Parker, Myra; Duran, Bonnie; Rhew, Isaac; Magarati, Maya; Egashira, Leo; Larimer, Mary; Donovan, Dennis
Abstract : Objectives: To examine the relationship between suicide risk and hazardous drinking, depression, and anxiety, adjusting for demographics, among tribal college students across the United States. Methods. We invited tribal college students enrolled in 22 tribal colleges from fall 2014 and 2015 to participate in the Creating Campus Change study, a cross-sectional online/paper survey assessing alcohol use patterns and mental health outcomes. 3, 239 students participated in the survey, yielding a response rate of 31.3%. We assessed alcohol use, depression, and general anxiety, along with demographic characteristics. We used the Mini-International Neuropsychiatric Interview to assess suicide risk. Results. 8.5% indicated moderate or high suicide risk. In the final adjusted model, moderate/high depression was significantly associated with moderate/high suicide risk (OR = 6.64; 3.91–11.28, p < 0.001), as was moderate/high general anxiety (OR = 2.80; 1.58–4.97, p < 0.001), and moderate/high hazardous drinking (OR = 2.09; 1.19–3.66, p < 0.001). Conclusions. Students attending tribal colleges who report moderate/high levels of depression, anxiety, or hazardous drinking have a greater risk of suicidality. Identifying factors buffering the risk of suicidality could support policy changes necessary to address this critical public health issue.